Contact-based motion graph and its application in locomotion synthesis for virtual actors. (2015) - Wei, Xiaopeng; Yi, Pengfei; Zhang, Qiang
To generate foot-skate free locomotion along user defined path for virtual actors, a novel data structure of contact-based motion graph is proposed. At first, sample motions are divided to contact clips according to the number of feet in contact with the ground. Then a directed graph can be built by producing nodes and basic edges based on these clips. After generating edges between nodes from different samples by linear interpolation, the contact-based motion graph can be defined as a strongly connected component of this graph. Applying synthesis strategy designed for nodes and edges, a path on contact-based motion graph can be converted to a smooth foot-skate free motion moving along the given path. The following experiments show the effectiveness of this method.